Asymmetric pass through of energy commodities to US sectoral returns. (June 2022) - Rehman, Mobeen Ur; Zeitun, Rami; Mardani, Abbas; Vo, Xuan Vinh; Eraslan, Veysel
Abstract: The influence of the international energy market on different economic aspects has increased significantly, especially after an escalation in the financialization of the energy market. Likewise following this trend, the relationship between the international energy market and the US sectoral returns has developed significantly since the last decade. We examine the presence of a non-linear relationship between major US sectors and energy commodities from January 2007 to December 2018. To rightly justify the application of non-linear estimation technique, we perform Narayan and Popp (2010) test followed by the Wald test to identify asymmetries in the model. These asymmetries are more pronounced in the coal market as compared to oil and gas markets. The results of NARDL model, which is capable of capturing the non-linear and asymmetric relationship, highlight the presence of asymmetries between the energy commodities and the US sectoral returns. This relationship is pronounced more in the short-run for all sectors. Our cumulative coefficients for representing the contemporaneous relationship between energy commodities and US sectoral returns also highlight not only consistent asymmetric behaviour in the short-run but show collective unitary positive and negative impact of oil, gas and coal market. As a robustness measure, our application of dynamic multipliers suggests that the relationship between energy commodities and US sectors converge in the long-run after 20–30 weeks' period. The results of our study entail valuable implications for policymakers and investors. Highlights: We investigate the impact of energy commodities in US sectoral returns. NARDL is used to capture the effect of unitary energy shocks on US sectoral returns. Results highlight presence of non-linear relationship more evident in short-run for all sampled US sectors. Relationship between energy and US sector converges towards long-run equilibrium position between 20 and 30 weeks.